2018
DOI: 10.1016/j.jas.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Copper ingots from a probable Bronze Age shipwreck off the coast of Salcombe, Devon: Composition and microstructure

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…4.4). Investigation of this site has also produced nearly 400 metal objects, comprising mainly copper and tin ingots (Wang et al 2016, 2018), along with weapons and gold objects, including several gold bar torc fragments. Several ships have been wrecked at this location (most recently in 1992), and there is a “high probability that two temporally distinct Bronze Age shipwrecks can be identified at Salcombe” (Wang et al 2016: 90).…”
Section: Scales and Weights From Middle And Late Bronze Age And Earlymentioning
confidence: 99%
“…4.4). Investigation of this site has also produced nearly 400 metal objects, comprising mainly copper and tin ingots (Wang et al 2016, 2018), along with weapons and gold objects, including several gold bar torc fragments. Several ships have been wrecked at this location (most recently in 1992), and there is a “high probability that two temporally distinct Bronze Age shipwrecks can be identified at Salcombe” (Wang et al 2016: 90).…”
Section: Scales and Weights From Middle And Late Bronze Age And Earlymentioning
confidence: 99%
“…The possible reasons for the occurrence of these waste could be explained as products of a final refining stage of a copper metallurgy. [ 64,65 ]…”
Section: Resultsmentioning
confidence: 99%
“…The possible reasons for the occurrence of these waste could be explained as products of a final refining stage of a copper metallurgy. [64,65] Type B, dating to the mid of 7 th to mid of the 6 th century BC, is mainly composed by copper with minor amounts of Sb, As, and Bi. These wastes are considered the remains of base-metal speiss, that is, a complex mixture of copper arsenides and antimonides, often containing sulfur and lead.…”
Section: Classification Of Slagsmentioning
confidence: 99%
“…Large plano-convex ingots are present in the greatest number in northwestern France (Brittany) (Boulud and Fily, 2009;Le Carlier de Veslud et al, 2014), and have a morphology similar to examples found in England (Wang et al, 2018). On the other hand, the small ingot is the most prevalent type found on the Iberian Peninsula (Montero Ruiz et al, 2011;Ramos, 1993).…”
Section: Introductionmentioning
confidence: 94%